2021
DOI: 10.1111/1471-0528.16669
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating diagnostic thresholds for intrahepatic cholestasis of pregnancy: case–control and cohort study

Abstract: Objective To determine the optimal total serum bile acid (TSBA) threshold and sampling time for accurate intrahepatic cholestasis of pregnancy (ICP) diagnosis. Design Case–control, retrospective cohort studies. Setting Antenatal clinics, clinical research facilities. Population Women with ICP or uncomplicated pregnancies. Methods Serial TSBA measurements were performed pre‐/postprandially in 42 women with ICP or uncomplicated pregnancy. Third‐trimester non‐fasting TSBA reference ranges were calculated from 561… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 28 publications
(66 reference statements)
4
42
0
6
Order By: Relevance
“…In our analysis, we found that TSBA concentrations for both groups of samples were not normally distributed, but rather had a positive skewness distribution, in accordance with other studies 26,28 (figure 1-2). We found a median of 7.6 μmol/L for the fasting TSBA with an upper reference limit (97.5 th percentile) of 14.1 μmol/L (95% CI 12.7-15.5 μmol/L).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In our analysis, we found that TSBA concentrations for both groups of samples were not normally distributed, but rather had a positive skewness distribution, in accordance with other studies 26,28 (figure 1-2). We found a median of 7.6 μmol/L for the fasting TSBA with an upper reference limit (97.5 th percentile) of 14.1 μmol/L (95% CI 12.7-15.5 μmol/L).…”
Section: Resultssupporting
confidence: 91%
“…We believe the strengths also include the prospective design, the accurate selection of eligible patients, the generalizability, and the clinical relevance of the results. Since no correlation has been reported between TSBA levels and gestational age within the third trimester 26 , our results could be applicable to the third trimester of pregnancy. The duration of the study over one year allowed us to evaluate the seasonality of TSBA levels.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…1 is based on the RCOG Green-top Guideline No. 43 from 2011 which is continually updated according to the most recent findings (see also Mitchell et al, 2021 78 and Ovadia et al 2021 79 ). When this article went to press, the RCOG had not yet updated its recommendations.…”
Section: Managementmentioning
confidence: 99%
“…1 basiert auf der RCOG Green-top Guideline No. 43. aus dem Jahr 2011 und wird fortlaufend entsprechend den aktuellen Erkenntnissen angepasst, siehe auch dazu Mitchell et al, 2021 78 und Ovadia et al 2021 79 . Bei Drucklegung dieses Artikels hat die RCOG die Empfehlungen überarbeitet.…”
Section: Managementunclassified